1990
DOI: 10.1007/bf00231257
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical study of the subcommissural organ of rats with induced postnatal hydrocephalus

Abstract: The subcommissural organ (SCO)-Reissner's fiber (RF) complex of rats suffering from postnatal hydrocephalus was investigated immunocytochemically (peroxidase-antiperoxidase technique) by use of an anti-serum against bovine RF. Hydrocephalus was induced by injecting kaolin into the cisterna magna or by intracerebral infection with Borna disease virus. The kaolin-injected, hydrocephalic male rats were divided into two groups: (1) possessing an open communication between the fourth ventricle and the central canal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…Olsson (1958a) and Oksche (1961) postulated that the hydrodynamic of the aqueductal CSF plays a role in the aggregation of the secreted material in the form of a typical RF. This hypothesis is supported by the fact that hydrocephalic rats do not form an RF (Irigoin et al, 1990). However, a recent finding in our laboratory supports the view that a CSF factor different from its hydrodinamic would participate in the assembly of the proteins into RF: the rat SCO grafted into a lateral ventricle of an intact rat forms a typical RF (unpublished observation).…”
Section: Pre-reissner's Fiber Stagementioning
confidence: 61%
See 1 more Smart Citation
“…Olsson (1958a) and Oksche (1961) postulated that the hydrodynamic of the aqueductal CSF plays a role in the aggregation of the secreted material in the form of a typical RF. This hypothesis is supported by the fact that hydrocephalic rats do not form an RF (Irigoin et al, 1990). However, a recent finding in our laboratory supports the view that a CSF factor different from its hydrodinamic would participate in the assembly of the proteins into RF: the rat SCO grafted into a lateral ventricle of an intact rat forms a typical RF (unpublished observation).…”
Section: Pre-reissner's Fiber Stagementioning
confidence: 61%
“…There is evidence that part of the SCO secretion released into the CSF remains soluble. Under certain physiological conditions, such as the embryonic period (chicken, rat, and human) and under specific experimental conditions, such as hydrocephalus, the SCO would secrete CSF-soluble compounds that do not form an RF, although they react with anti-RF sera (Irigoin et al, 1990;Schöebitz et al, 1993).…”
Section: Csf-soluble Secretory Materialsmentioning
confidence: 99%
“…The human SCO has a great development during the foetal life [8,9], variations in the CSF and SCO have been reported in different kinds of hydrocephalus [4,10,11]. Alterations of the SCO in hydrocephalic mice and rats have been described, Takeuchi et al [12] de-scribes agenesis of the SCO and the posterior commissure (PC) in hydrocephalic mice, Irigoin et al [11], Rodriguez et al [4] and Carmona-Calero et al [7] found alterations in the secretion of the SCO in induced and spontaneously hydrocephalic rats. In addition, alterations in the secretions of cerebrospinal fluid proteins from the SCO have been described in spontaneously hypertensive rats [6].…”
Section: Introductionmentioning
confidence: 99%
“…In regards to its main function, CSF overproduction by the choroid plexus is a rare a cause of hydrocephalus [3] [8] [241]. [252] and exhibits decreased glycoprotein immunoreactivity [253], and the subfornical organ can become damaged as the condition progresses [254].…”
Section: Choroid Plexusmentioning
confidence: 99%